Internalized homophobia and sexual risk behavior in men who have sex with men: The mediational role of sexual self-concept - Sepúlveda-Páez, Geraldy; Santibañez-Palma, J. Francisco; Ferrer-Urbina, Rodrigo; Atencio, Diego; Bucarei, Patricia; Castillo, Jenifer; Fuentes, Matías; Zumarán, Bárbara (Frontiers in Psychology, 2022)
Men who have sex with men (MSM) are one of the populations most likely to be infected with human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) worldwide. Sexual risk behaviors (SRB) are the main route of HIV transmission. Among the factors associated with SRB, internalized homophobia (rejection of one’s sexuality) is a risk factor unique for MSM. However, how this factor influences SRB is not clear. Therefore, the present study attempts to clarify the mechanism of action of the relationship between internalized homophobia on SRB based on the mediating effects of sexual self-concept. A study was conducted with 124 MSM living in Chile over 18 years of age (M = 24.4 and SD = 4.19). Through path analysis, it was observed that internalized homophobia has slight inverse effects on SRBs (multiple sexual partners and sexual activity under the influence of alcohol or drugs) when the sexual self-efficacy dimension acts as a mediating variable. These findings suggest that developing sexually transmitted infections (STIs) and HIV/AIDS prevention campaigns focused on MSM must highlight the development of a healthy sexual self-concept and address self-stigma.